The process of risk management: sketching the providers of Islamic micro- finance - Awais, Muhammad; Mohd Thas Thaker, Mohamed Asmy; Raza, Asif; Usman, Usama; Mohsin, Muhammad; Khalid Bhatti, Omar (Ponte Academic Journal, 2021)
With the assistance of using comparative analysis and interviews, we have formulated study on two discreet types of Islamic microfinance institutions: Non-government organizations & Commercial financial institutions. This has relatively been done with the help of taking into consideration the systematic disbursement and repayment methods. Conclusively, both of the companies were susceptible to Shariah risk, operational risk and credit risk. Furthermore, company B has a well renowned goodwill in the market therefore, it is prone to reputational risk as well.